2020
DOI: 10.1111/jcmm.16158
|View full text |Cite
|
Sign up to set email alerts
|

Naringin attenuates cisplatin‐ and aminoglycoside‐induced hair cell injury in the zebrafish lateral line via multiple pathways

Abstract: Ototoxicity refers to the pathological and functional impairments of auditory nervous system caused by the application of some therapeutic drugs. Although drug-induced hearing loss is not fatal, it will seriously damage the social and health-related quality of patients, with significant implications for careers, education and society. In children, even minor hearing loss can impede speech, language, cognition and social development, which can lead to poor academic performance and psychosocial functioning. 1-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The relationship between cisplatin and oxidative stress has been well established ( Gentilin et al, 2019 ; Kros and Steyger, 2019 ; Sheth et al, 2017 ), and prior studies demonstrate that mitochondria play a key role in cisplatin-induced oxidative stress in cancer and non-cancer cell lines ( Marullo et al, 2013 ) as well as hair cells ( Li et al, 2021 ; Lu et al, 2022 ). Here, we build on this literature and demonstrate that oxidative stress occurs shortly after cisplatin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cisplatin and oxidative stress has been well established ( Gentilin et al, 2019 ; Kros and Steyger, 2019 ; Sheth et al, 2017 ), and prior studies demonstrate that mitochondria play a key role in cisplatin-induced oxidative stress in cancer and non-cancer cell lines ( Marullo et al, 2013 ) as well as hair cells ( Li et al, 2021 ; Lu et al, 2022 ). Here, we build on this literature and demonstrate that oxidative stress occurs shortly after cisplatin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, naringin may possess potential roles in treating various diseases, such as osteoporosis and degenerative disorders of different tissues, including neurons, because this phytochemical is able to stimulate MSC proliferation and lineage differentiation . In contrast, naringin had opposite bioactivity in a variety of cancer cells of inhibiting cell proliferation or even killing drug-sensitive or -resistant tumor cells via multiple signal-transducing mechanisms. , For example, naringin suppressed osteosarcoma cell proliferation and metastasis . Results of a MTT assay also demonstrated that naringin increased mitochondrial succinate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…46 In contrast, naringin had opposite bioactivity in a variety of cancer cells of inhibiting cell proliferation or even killing drug-sensitive or -resistant tumor cells via multiple signal-transducing mechanisms. 47,48 For example, naringin suppressed osteosarcoma cell proliferation and metastasis. 49 Results of a MTT assay also demonstrated that naringin increased mitochondrial succinate dehydrogenase activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, the need for effective otoprotectants exists, and the hair cells of the zebrafish larvae are a useful model to speed up that goal ( Ton and Parng, 2005 ). Some of the mentioned antioxidant compounds have been positively tested against ototoxins in zebrafish larvae, like glutathione, allopurinol, N-acetylcysteine, D-methionine ( Ton and Parng, 2005 ), L-Serine ( Monroe et al, 2021 ), a curcuminoid ( Monroe et al, 2018 ), flavonoids, like naringin ( Li et al, 2021 ) or quercetin ( Lee et al, 2015 ; Hirose et al, 2016 ), a small peptide ( Xiao et al, 2018 ), or ferrostatin ( Hu et al, 2020 ).…”
Section: Screening For Hair Cell Protectorsmentioning
confidence: 99%